2017
DOI: 10.3390/ijms18081770
|View full text |Cite
|
Sign up to set email alerts
|

Role of Omentin, Vaspin, Cardiotrophin-1, TWEAK and NOV/CCN3 in Obesity and Diabetes Development

Abstract: Adipose tissue releases bioactive mediators called adipokines. This review focuses on the effects of omentin, vaspin, cardiotrophin-1, Tumor necrosis factor-like Weak Inducer of Apoptosis (TWEAK) and nephroblastoma overexpressed (NOV/CCN3) on obesity and diabetes. Omentin is produced by the stromal-vascular fraction of visceral adipose tissue. Obesity reduces omentin serum concentrations and adipose tissue secretion in adults and adolescents. This adipokine regulates insulin sensitivity, but its clinical relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 165 publications
(256 reference statements)
2
62
1
3
Order By: Relevance
“…While most of the recent studies on vaspin have focused on its physiological function, only few studies have reported the basis for regulation of the vaspin gene [13,14]. Although vaspin mRNA expression of diabetic OLETF rats was restricted to visceral white adipose tissue, mouse vaspin mRNA was highly expressed in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the recent studies on vaspin have focused on its physiological function, only few studies have reported the basis for regulation of the vaspin gene [13,14]. Although vaspin mRNA expression of diabetic OLETF rats was restricted to visceral white adipose tissue, mouse vaspin mRNA was highly expressed in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic implications of this adipokine and others, is of great interest in the field of diabetes mellitus and obesity [32].…”
Section: Discussionmentioning
confidence: 99%
“…CT-1 is a member of the interleukin-6 superfamily, which is expressed in different tissues including the heart, vessels, skeletal muscle, liver, lung, adipose tissue, and kidney [58,59]. In the myocardium, CT-1 is produced by both cardiomyocytes and fibroblasts, exerting its action through the glycoprotein 130 (gp130)/ leukemia inhibitory factor receptor (LIFR) heterodimer.…”
Section: Cardiotrophin-1 41 Cardiotrophin-1 Induces Fibrosis and Infmentioning
confidence: 99%